Optimal Airport Selection for Iraq's Infrastructure Development: A TOPSIS Analysis - Naser, Farah K.; Khaleel, Tareq A. (Engineering, Technology & Applied Science Research, 2024)
This study investigates the application of the Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS) method to enhance Iraq's airport infrastructure. The research aims to analyze the performance of major airports based on data collected from the Central Statistical Organization (CSO) of Iraq. A model is proposed to prioritize the airport development projects based on essential criteria, such as aircraft movement (landing and takeoff) and passenger movement (arrivals and departures). The airports are ranked according to the priority they have in infrastructure development, which is linked to their economic growth. In terms of priority, the first is Baghdad International Airport, Basra Airport follows, and Najaf Airport ranks third. Erbil and Sulaymaniyah airports rank lower due to infrastructure limitations and administrative challenges. The research underscores the importance of ongoing investments in airport infrastructure to accommodate the increasing number of passengers and bolster economic expansion.